Towards a better diagnosis and treatment of Rett syndrome: a model synaptic disorder - Banerjee, Abhishek; Miller, Meghan T; Li, Keji; Sur, Mriganka; Kaufmann, Walter E (Brain (London, England : 1878), 2019)
With the recent 50th anniversary of the first publication on Rett syndrome, and the almost 20 years since the first report on the link between Rett syndrome and MECP2 mutations, it is important to reflect on the tremendous advances in our understanding and their implications for the diagnosis and treatment of this neurodevelopmental disorder. Rett syndrome features an interesting challenge for biologists and clinicians, as the disorder lies at the intersection of molecular mechanisms of epigenetic regulation and neurophysiological alterations in synapses and circuits that together contribute to severe pathophysiological endophenotypes. Genetic, clinical, and neurobiological evidences support the notion that Rett syndrome is primarily a synaptic disorder, and a disease model for both intellectual disability and autism spectrum disorder. This review examines major developments in both recent neurobiological and preclinical findings of Rett syndrome, and to what extent they are beginning to impact our understanding and management of the disorder. It also discusses potential applications of knowledge on synaptic plasticity abnormalities in Rett syndrome to its diagnosis and treatment.